Іnfluence of abiotic environmental factors on liver function disorders and methods of their prevention in cows - Magrelo, N. V.; Kozenko, O. V.; Sus, H. V. (Baltija Publishing, 2022)
Currently, the ecological state of the environment is one of the global problems of humanity on almost all continents. Through the significant progress of science and technology, the mechanization of the main production processes in various branches of the national economy. With new production technologies, conditions are created for an increase in the number of harmful substances in the environment, the toxic effect of which on living organisms is beyond doubt. It is facilitated by the pursuit of cheap products and materials, the imperfect technology of their production, and the desire to obtain excess profits, which, on par with the threat of global warming, creates hazardous conditions for all humanity. In addition, a person who has tamed many species of animals and receives considerable benefit from them is in outstanding debt to them. Therefore, man must feed and protect them from harmful factors and, first of all, the environment he created.
Topical issues of the development of veterinary medicine and breeding technologies : scientific monograph.
Keywords: liver in cows; печінка корів